2009
DOI: 10.1302/0301-620x.91b10.22094
|View full text |Cite
|
Sign up to set email alerts
|

Does arthroscopic acromioplasty provide any additional value in the treatment of shoulder impingement syndrome?

Abstract: We report a randomised controlled trial to examine the effectiveness and cost-effectiveness of arthroscopic acromioplasty in the treatment of stage II shoulder impingement syndrome. A total of 140 patients were randomly divided into two treatment groups: supervised exercise programme (n = 70, exercise group) and arthroscopic acromioplasty followed by a similar exercise programme (n = 70, combined treatment group). The main outcome measure was self-reported pain on a visual analogue scale of 0 to 10 at 24 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
122
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 35 publications
(40 reference statements)
2
122
2
6
Order By: Relevance
“…Our study indicates that using self-reported pain (by VAS) or secondary outcome measures at 2 or 5 years for analysis, the effects of combined treatment did not differ significantly from the effects of treatment with supervised exercise alone. In this study we did not compare the overall effects of these 2 modes of treatment, but specifically analyzed the eventual additional value provided by the operation over and beyond the effect obtained using a structured and supervised exercise program alone (Ketola et al 2009 and 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study indicates that using self-reported pain (by VAS) or secondary outcome measures at 2 or 5 years for analysis, the effects of combined treatment did not differ significantly from the effects of treatment with supervised exercise alone. In this study we did not compare the overall effects of these 2 modes of treatment, but specifically analyzed the eventual additional value provided by the operation over and beyond the effect obtained using a structured and supervised exercise program alone (Ketola et al 2009 and 2013).…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had had previous shoulder surgery. The inclusion and exclusion criteria and the precise study protocol are described in the report of the 2-year results (Ketola et al 2009). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations